RELIABILITY ANALYSIS OF MEDICAL EQUIPMENT BASED ON q-WEIBULL DISTRIBUTION (MT) - FAN LiTian; WANG HaoWen; LING QingQing; CHEN HongWen (Jixie qiangdu)
A reliability analysis of medical equipment is implemented based on the q-Weibull distribution to provide a basis for healthcare organizations to revise their operational maintenance management strategies. The Weibull distribution failure rate function is monotonic and cannot fully describe the full life cycle operation of complex medical equipment. Therefore, this study introduces the q-Weibull distribution to predict the remaining life of medical equipment, uses a method based on the contour error function to simplify the q-Weibull distribution parameter estimation process, and verifies the validity and feasibility of the method using a hemofiltration apparatus and a lamp-holder of surgical shadowless lamp as examples, and compares the advantages and disadvantages of the two distributions by mean square error（MSE）, the Akaike information criterion（AIC） and the coefficient of determination R~2. Both distributions for the hemofiltration apparatus and lamp-holder of surgical shadowless lamp show the same predictive trend, but the R~2 and MSE comparisons show that the q-Weibull distribution had a better fit accuracy, especially the MSE(2.818 1×10-3)for the hemofiltration apparatus based on the q-Weibull distribution is much smaller than the MSE（9.465） for the Weibull distribution. When the hemofiltration apparatus and lamp-holder of surgical shadowless lamp are operated for 50 days, their estimated remaining life is 254.390 9 days and 291.011 1 days respectively. The above data verifies the validity and fitting accuracy of the q-Weibull distribution, which is worthy of further research and promotion in the reliability research of medical equipment.